2007
DOI: 10.1016/j.cellbi.2006.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Cajal bodies and interchromatin granule clusters in cricket oocytes: Composition, dynamics and interactions

Abstract: The organization and molecular composition of complicated Cajal bodies (CBs) and interchromatin granule clusters (IGCs) in oocytes of the house cricket, Acheta domesticus, were studied using immunofluorescent/confocal and Immunogold labeling/electron microscopy. In A. domesticus oocytes, the CB consists of the fibrillar matrix and a central cavity containing a predominantly granular body with insertions of tightly packed fibrillar material. The latter structure was identified as an "internal" IGC, since it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…It should be also noted that P. communis diplotene oocytes used in this study are transcriptionally inert [17] and, in contrast to the active cells, the IGC granules of P. communis oocytes could be the storage sites for the Pol II holoenzyme components disengaged from transcription. The same function of IGCs in inactive insect oocytes was discussed earlier [6,8]. Additionally, our data on tight association of transcriptional coactivators CBP/p300 with granules of IGCs in P. communis oocytes (Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…It should be also noted that P. communis diplotene oocytes used in this study are transcriptionally inert [17] and, in contrast to the active cells, the IGC granules of P. communis oocytes could be the storage sites for the Pol II holoenzyme components disengaged from transcription. The same function of IGCs in inactive insect oocytes was discussed earlier [6,8]. Additionally, our data on tight association of transcriptional coactivators CBP/p300 with granules of IGCs in P. communis oocytes (Fig.…”
Section: Resultssupporting
confidence: 85%
“…The nature of some characteristic inclusions observed in oocytes of different insects as the CBs are established now [2][3][4][5] whereas until recently little is known about insect oocyte IGC structure and functions. Insect oocyte IGCs have been described only in a beetle [6,7], the house cricket [8], a fleshfly [9] and some bugs [10]. In our previous study, we showed some features of IGC structure and molecular composition in oocyte nuclei of the scorpionfly, Panorpa communis [11].…”
Section: Introductionmentioning
confidence: 92%
“…Unfortunately, we still know very little about this subject. To date, IGC counterparts have been described only in some insects including the mealworm beetle, (37,38) the scorpionfly, (39) the house cricket, (40) some bugs, (41) and a fleshfly; (42) however, other ''granular'' NBs, resembling IGCs but of an unknown nature, have also been described in the oocytes of Drosophila, (43) the tse-tse fly, (44) and the dragonfly. (45) In many cases, insect oocyte IGCs possess peculiarities that make them somewhat different from the ''classic'' IGCs of mammalian somatic cells.…”
Section: The Interchromatin Granule Clustera Constantly Upgraded Orgamentioning
confidence: 99%
“…(77) The transcription coactivators CBP/p300 and the basal transcription factor TBP have also been revealed in oocyte CBs from the house cricket. (40) The essential splicing factor SC35 and other SR proteins have not been found in mammalian CBs. (5) However, we have repeatedly debated their presence, together with that of snRNPs, in oocyte CBs from various insects.…”
Section: The Cb Is a Sea Of Compoundsmentioning
confidence: 99%
See 1 more Smart Citation